1985
DOI: 10.1177/0265407585022004
|View full text |Cite
|
Sign up to set email alerts
|

Premarital Relationship Correlates of the Erosion of Satisfaction in Marriage

Abstract: The results of the present study show that premarital conflict is a precursor of marital conflict and that, while it does not relate to the feelings that partners report having about one another premaritally, it does predict the extent to which they are satisfied once they have been married about two and a half years. Twenty-one newlyweds provided detailed time-ordered descriptions of their courtships, dividing them into three stages of involvement - casual dating, serious dating, and commitment to marriage. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(46 citation statements)
references
References 11 publications
2
43
0
1
Order By: Relevance
“…То, как люди выбирают брачного партнера, различные стили и продолжительность до-брачного ухаживания, решение о сожительстве до брака -все это влияет на его последующее развитие. Некоторые начинают исследовать эти вопросы с помощью ретроспективного плана исследования [Kelly, Huston, Cate, 1985;Surra, Arizzi, Asmussen, 1988]. Но проспективные данные, полученные в результате сопровож-дения выборки, состоящей из пар от этапа свиданий или ухаживания до свадь-бы и после, позволят изучить, как переход к браку влияет на его последующее развитие.…”
Section: исследовательские приоритетыunclassified
“…То, как люди выбирают брачного партнера, различные стили и продолжительность до-брачного ухаживания, решение о сожительстве до брака -все это влияет на его последующее развитие. Некоторые начинают исследовать эти вопросы с помощью ретроспективного плана исследования [Kelly, Huston, Cate, 1985;Surra, Arizzi, Asmussen, 1988]. Но проспективные данные, полученные в результате сопровож-дения выборки, состоящей из пар от этапа свиданий или ухаживания до свадь-бы и после, позволят изучить, как переход к браку влияет на его последующее развитие.…”
Section: исследовательские приоритетыunclassified
“…The conflict scale consists of five items that assess the amount and intensity of conflict in the marital relationship (e.g., "How often do you and your partner argue with one another"). The conflict scale was used because it has been found to be an important predictor of relationship quality (Kelly, Huston, & Cate, 1985) and has been previously related to children's emotion regulation in toddlerhood (Belsky, Youngblade, Rovine, & Volling, 1991). Previous studies have found Cronbach's alphas for the Braiker-Kelley conflict scale between .61 and .92 across mothers and fathers the third trimester of pregnancy of a child until the third year of life (Belsky et al, 1991).…”
Section: Marital Conflictmentioning
confidence: 99%
“…In the first few months of marriage, associations between marital quality and spouses' conflictive interactions are nonsignificant or small in magnitude (Huston et al, 1986;Huston and Vangelisti, 1991). Significant, and negative, associations between marital quality and conflictive interactions begin to emerge approximately 1 to 2 years into marriage (Huston et al, 1986;Kelly et al, 1985) and continue to increase in magnitude over time, at least through the first 5 years of marriage (Markman, 1981). Thus, there is a "sleeper effect" (Kelly et al, 1985;Markman, 1981) whereby associations between spouses' conflict and marital quality emerge only after a couple has been married for some time and then continue to increase in magnitude at least several years into thc relationship.…”
Section: Introductionmentioning
confidence: 99%
“…Significant, and negative, associations between marital quality and conflictive interactions begin to emerge approximately 1 to 2 years into marriage (Huston et al, 1986;Kelly et al, 1985) and continue to increase in magnitude over time, at least through the first 5 years of marriage (Markman, 1981). Thus, there is a "sleeper effect" (Kelly et al, 1985;Markman, 1981) whereby associations between spouses' conflict and marital quality emerge only after a couple has been married for some time and then continue to increase in magnitude at least several years into thc relationship. It follows that associations between trait hostility and marital quality may be obscured or weakened in studies that employ couples who have been married for varying lengths of time or that do not account for length of marriage either methodologically or statistically.…”
Section: Introductionmentioning
confidence: 99%